2004
DOI: 10.1262/jrd.50.171
|View full text |Cite
|
Sign up to set email alerts
|

Activation with Ethanol Improves Embryo Development of ICSI-Derived Oocytes by Regulation of Kinetics of MPF Activity

Abstract: Abstract. Developmental potential of bovine embryos that are not artificially activated after intracytoplasmic sperm injection (ICSI) is generally very low. In this study, we investigated effects of artificial activation with ethanol on kinetics of maturation promoting factor (MPF) activity (p34 cdc2 kinase activity) and development of bovine oocytes following ICSI. Treatment of oocytes with ethanol at 4 h after ICSI improved their first cleavage and further preimplantation development (51% vs. 13%, 14% vs. 4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 34 publications
4
31
0
2
Order By: Relevance
“…This blastocyst yield is comparable to or even higher than those in many reports where bovine oocytes harvested from freshly collected ovaries were used for ICSI [8,10,11,[13][14][15][16]. Simultaneously with the ICSI experiments in the present study, high blastocyst yield (40 ± 3%, 90/223) was obtained after routine 225 IVF protocol, suggesting that oocytes harvested from stored ovaries carry sufficient in vitro developmental potential after IVF and ICSI if they were subjected to appropriate activation regimen.…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…This blastocyst yield is comparable to or even higher than those in many reports where bovine oocytes harvested from freshly collected ovaries were used for ICSI [8,10,11,[13][14][15][16]. Simultaneously with the ICSI experiments in the present study, high blastocyst yield (40 ± 3%, 90/223) was obtained after routine 225 IVF protocol, suggesting that oocytes harvested from stored ovaries carry sufficient in vitro developmental potential after IVF and ICSI if they were subjected to appropriate activation regimen.…”
Section: Discussionsupporting
confidence: 55%
“…The blastocyst yield in non-treated group (12%) is higher than those (0-8%) reported previously by several laboratories [8,10,11,[14][15][16], but comparable to or even lower than those (15-23%) in other reports [12,13]. However, blastocysts/ 235 cleavage rate in our study (30%) is comparable to that reported by Wei and Fukui [12] (32%) which indicates that a failure in the early post-fertilization events -from fertilization until cleavage-is the main determiner to the successful development after bovine ICSI.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations